The Effect Of Audit Opinion, Reputation Of Public Accountant Firm, Audit Delay, Company Size, And Financial Distress On Auditor Switching - Bagaskara, Kurniarga; Indraswono, Cahyo (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This study aims to prove whether there is an effect of audit opinion, reputation of public accountant firm, audit delay, company size, and financial distress on auditor switching in the infrastructure, utilities, and transportation also healthcare sectors listed on the Indonesian Stock Exchange (IDX) in 2016-2019. In this study, company size variable is measured using natural logarithms and financial distress is measured using the debt-to-equity ratio (DER). The data obtained are in the form of financial reports that can be downloaded through the company’s official website and IDX’s official website, www.idx.co.id. The sample selection process was carried out using purposive sampling and obtained a sample of 21 companies with a period of 4 years. Hypothesis in this research are tested by logistic regression analytical method and probit model. The result of this study indicate that audit delay has a positive effect on auditor switching, while audit opinion, reputation of public accountant firm, company size, and financial distress has no effect on the auditor switching